2006
DOI: 10.1152/japplphysiol.01101.2005
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin-induced activation of pulmonary vagal C fibers produces reflex laryngeal closure in the rat

Abstract: Our recent studies show that intravenous administration of capsaicin induces enhancement of the intralaryngeal thyroarytenoid (TA) branch but a reduction of the intralaryngeal abducent branch, suggesting that the glottis is likely closed by capsaicin. The aim of the present study was to examine whether the glottis is adducted by intravenous administration of capsaicin. Electromyographic (EMG) activity of the TA muscle, subglottal pressure (SGP), and glottal behavior were evaluated before and after intravenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
(47 reference statements)
1
9
0
Order By: Relevance
“…However, anandamide also induced a concomitant increase in burst amplitude with earlier onset in the adducent branch of the RLN. This coordinated response of the RLN branches resulted in a short period of glottal closure (47), similar to that reported in response to capsaicin (34). Moreover, a similar response occurs during pulmonary edema in lambs (8,9).…”
Section: Capsaicin Injection Inhibits Facial Motor Outputsupporting
confidence: 82%
“…However, anandamide also induced a concomitant increase in burst amplitude with earlier onset in the adducent branch of the RLN. This coordinated response of the RLN branches resulted in a short period of glottal closure (47), similar to that reported in response to capsaicin (34). Moreover, a similar response occurs during pulmonary edema in lambs (8,9).…”
Section: Capsaicin Injection Inhibits Facial Motor Outputsupporting
confidence: 82%
“…While there were upper outliers in these data that were excessive, the mean subglottal pressures observed were biologically realistic. 13 A significant main effect for adduction condition was found at airflow rates of 3 L/min (F ͓2,4͔ = 14.88, p = 0.01), 4 L/min (F ͓2,6͔ = 54.75, p = 0.0001), and 6 L/min (F ͓2,7͔ = 11.69, p Ͻ 0.01). Post-hoc paired comparisons revealed that modal frequency was significantly greater in both the anterior and the anterior/posterior adduction conditions at airflow rates of 3, 4, and 6 L/min compared with the open glottis condition ͑p Ͻ 0.05͒.…”
Section: Resultsmentioning
confidence: 93%
“…Although direct study of subglottal pressure during USV production is lacking, one study of rats reported subglottal pressures of 30 cm H 2 O during vocal fold closure. 13 Thus, it is likely that variations in laryngeal adduction, airflow, and subglottal pressure are used by the rat to achieve a wide frequency range of USVs in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 The endogenous opioid peptide-related behavior modulation may be disrupted with digoxin toxicity. 40 Digitalis toxicity may disrupt the sympathovagal control network, 41 which could lead to respiratory arrest due to vagal paralysis 42 and SAH probably due to hypothalamic damage. 12,43 Glycosides may be transported to the cerebrospinal fluid via choroidal arteries in patients with SAH.…”
Section: Discussionmentioning
confidence: 99%